Effective writing in psychology : papers, posters, and presentations - Beins, Bernard; Beins, Agatha, 1976- (Hoboken, NJ: John Wiley & sons, 2021)
"When you write about psychology or any of the other sciences, you are telling a story about people. Scientists are people, complete with individual personalities, likes and dislikes and ordinary human qualities. The way they are affects what they do and how they do it. As such, "science writing is not so much about science, but about people-human problems and their solutions, curiosity and discovery" (Holland, 2007). In this book, you will learn how to convey your thoughts on the important problems and solutions in psychology. It would be hard to overstate how important it is to write effectively. Writing constitutes one of the "3 Rs" of a basic education: reading, writing and 'rithmetic. In the world of business, success is dependent, in part, on effective writing. For high-level positions, "writing is a 'threshold skill' for both employment and promotion" (College Board, 2004, p. 3). In one survey, many companies noted that writing was important in hiring. One respondent asserted that, "in most cases, writing ability could be your ticket in ... or it could be your ticket out" (College Board, 2004, p. 3). Potential employees who do not write well are unlikely to be hired and, if they are, are unlikely to be promoted"--
Revised edition of the authors' Effective writing in psychology, 2012.
Includes bibliographical references (pages 283-294) and indexes.
Keywords: Psychology -- Authorship